The effect of de-hubbing on airfares. (January 2016) - Tan, Kerry M.; Samuel, Andrew
Abstract: This paper studies the price effect of de-hubbing, which occurs when an airline ceases hub operations at an airport. We develop a simple theoretical model to study the impact of de-hubbing on prices and quantities of direct flights at the hub airport. Using an event study of seven cases of de-hubbing between 1993 and 2009, we analyze how average airfares change following de-hubbing. Consistent with the theoretical implications, the empirical results suggest that airfares decrease when there is a low-cost carrier presence at the de-hubbed airport, whereas airfares increase when the de-hubbed airport is not serviced by a low-cost carrier. Highlights: We analyze how airfares change following de-hubbing by a legacy carrier. We perform an event study of seven cases of de-hubbing between 1993 and 2009. Average airfares decrease if the de-hubbed airport is serviced by low-cost carriers. Average airfares increase if no low-cost carriers is present at the de-hubbed airport. A model provides theoretical hypotheses that are consistent with the empirical findings.